Early mosques in West Africa and the Swahili coast: the role of Ibadi and Ismaili communities - Pradines, Stéphane (2021)
Mosques are one of the physical representations of Islam and of Muslim communities in the archaeological record. The workshop will present a number of archaeological case studies in the Levant, the...
Keywords: Zanzibar

Livingstone et la "plaie ouverte du monde" - Barbier-Mosimann, Marie-Claude (Historia, 2021)
Keywords: Zanzibar

Voyages sans retour pour Zanzibar - Barbier-Mosimann, Marie-Claude (Historia, 2021)
Keywords: Zanzibar

The Oral Art of Soqoṭra : A Collection of Island Voices - Morris, Miranda (Brill, 2021)
In the bilingual English-Arabic work, The Oral Art of Soqoṭra: A Collection of Island Voices, Miranda Morris and Ṭānuf Sālim Di-Kišin, in collaboration with Soqoṭrans from all parts of the island, present over a thousand examples of poems and songs, prayers, lullabies, work-chants, messages in code, riddles, examples of community wisdom encapsulated in poetic couplets, and stories centred on a short poem or exchange of poems. These were documented by oral transmission directly to the authors, or through recordings collected by them. They are presented in Soqoṭri (transcribed phonetically in Roman and in Arabic script), and in English and Arabic translation.
Keywords: Zanzibar